Natural solutions for glowing skin: spices - Ozler, Ebru; Sanlier, Nevin (Frontiers in Nutrition, 2025)
Skin aging, a biological process that occurs with changes in skin appearance as a result of a decrease in physiological functions, is among the important problems of modern times for both women and men. Spices can alleviate skin aging due to their rich contents of bioactive compounds, including antioxidants and polyphenols, and can reduce the oxidative stress and inflammation that contribute to skin aging. It is thought that the antioxidant and anti-inflammatory effects of the bioactive components in spices may have positive effects on skin health with anti-aging properties. Some spices achieve protective effects against skin aging by reducing the negative effects of ultraviolet (UV) rays, proinflammatory cytokines, tyrosinase, and melanin synthesis, as well as inhibiting collagenase and elastase activity, suppressing the messenger ribonucleic acid (mRNA) expression of matrix metalloproteinases, and increasing collagen synthesis. This review addresses the promising anti-aging benefits of spices for skin health and offers some suggestions for future research.